(untitled) (Research, Society and Development, 2022)
Introduction: Health and well-being are increasingly frequent concerns in modern society and the practice of sports is a fundamental point in this routine. Over the last century, we can see a huge growth in the variety of extreme sports such as boxing, wrestling (free martial arts and football) and in the number of participants. These sports are of great impact and even the most traditional modalities gain new supporters day after day, and with that the number of sports-related injuries grows. Objective: To establish the role of the physical therapist in the treatment of sports injuries. Methodology: Review of articles related to the study of specific knowledge of physical therapists on the prevention of pathologies that occur in sports. Outcomes: The physical therapist has specific knowledge of athlete rehabilitation and sports and, as such, is better able to help athletes recover quickly. Injuries caused by sport occur while participating in competitions or even during training sessions. The role of the physical therapist in the treatment of these sports injuries to the brain skull, caused by trauma or shock due to the speed of impact and the aggressiveness of the sport, becomes increasingly favorable. Conclusion: A strong athlete-physiotherapist relationship is necessary for effective treatment and the definition of athletes’ expectations regarding injury rehabilitation when possible.